APLIKASI PENDAFTARAN SEMINAR BERBASIS FRAMEWORK CODEIGNITER QRCODE-MOBILE DI STMIK ICHSAN GORONTALO: APLIKASI PENDAFTARAN SEMINAR BERBASIS FRAMEWORK CODEIGNITER QRCODE-MOBILE DI STMIK ICHSAN GORONTALO - ona Maliki; Farid (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
The problem faced is difficulty registering participants only recorded in the notebook, so it takes a long time. It is feared that there are many queues at the registration location. Codeigniter is one of the best frameworks available today. Many major websites have used Codeigniter as the main framework for building websites and applications. The result of this study is that it can help participants who want to attend national seminars efficiently in terms of cost and effectiveness in terms of time. The obstacles faced are the difficulty of registering participants only in the notebook. Hence, it takes a long time, and it is feared that there will be many queues at the registration location. Codeigniter is one of the best frameworks today, and many large websites have used CodeIgniter as the main framework for building websites and applications.The method used by the author in this final project is Research and Development (R&D), which is research used to produce seminar registration applications obtained offline and online and test the effectiveness of products. The results of this study can help participants who want to attend national seminars efficiently in terms of cost and effectiveness in terms of time.